Medium. The fourth season [videorecording (DVD)] - Arquette, Patricia, 1968-; Weber, Jake, 1964-; Sandoval, Miguel, 1951-; Cubitt, David, 1965-; Vassilieva, Sofia, 1992-; Lark, Maria, 1997-; DuBois, Allison (Paramount Home Entertainment, 2008)
Psychic Allison Dubois is a Phoenix wife and mother who struggles to make sense of her dreams. This season, Allison's world is turned upside down when her abilities are revealed to the public. Her boss, Manuel Devalos, is ousted from office, and detective Lee Scanlon won't return her calls. But as she and husband Joe--also newly unemployed--struggle to survive and care for toddler Marie and eldest daughters Ariel and Bridgette, Allison knows one thing-- her dreams will never fail her.